Using Lotus Notes as an intranet. - Falkner, Mike, 1954- (John Wiley & Sons, Inc., 1997)
On the CD-ROM you'll find: 25 Lotus Notes Databases for use with the Notes/Domino™ server technology. Great Plains® Dynamics accounting software with Notes integration.